The Medical Ethics (KYAMC Journal, 2017)
The medical ethics means the moral principles, which should guide the members of medical profession in course of their practice of medicine and their dealings with patient and other members of the same profession. Medical etiquette deals with the conventional laws of courtesy observed between members of the medical profession.KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 810-813